2010
DOI: 10.1111/j.1553-2712.2010.00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefit of Transfer to Tertiary Trauma Centers for Major Trauma Patients Initially Presenting to Nontertiary Trauma Centers

Abstract: Objectives: Recent evidence suggests a measurable reduction in mortality for patients transferred from a nontertiary trauma center (Level III or IV) to a Level I trauma center, but not for those transferred to a Level II trauma center. Whether this can be generalized to a predominantly rural region with fewer tertiary trauma care resources is uncertain. This study sought to evaluate mortality differences for patients initially presenting to nontertiary trauma centers in a predominantly rural region depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
97
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(102 citation statements)
references
References 24 publications
5
97
0
Order By: Relevance
“…Regionalization of care to specialized institutions, capable of providing life saving interventions, allows TBI patients to capitalize on the above developments. [2][3][4][5] Timely inter-hospital transfers to level I and II trauma centers, after evaluation in the emergency department (ED) of lower level centers, have been associated with improved survival. [2][3][4][5] In this setting, the influence of non-medical factors in the decision to transfer TBI patients, initially seen in less specialized institutions, to higherlevel trauma centers remains an issue of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Regionalization of care to specialized institutions, capable of providing life saving interventions, allows TBI patients to capitalize on the above developments. [2][3][4][5] Timely inter-hospital transfers to level I and II trauma centers, after evaluation in the emergency department (ED) of lower level centers, have been associated with improved survival. [2][3][4][5] In this setting, the influence of non-medical factors in the decision to transfer TBI patients, initially seen in less specialized institutions, to higherlevel trauma centers remains an issue of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Injury treatment at designated trauma centers can reduce mortality from traumatic injury, [1][2][3][4] but the majority of US residents in rural areas do not have timely access to Level I or II trauma centers. 5 Geographic barriers to trauma care are more likely to impact racial minorities and people living in poverty, 6 paralleling established racial and socioeconomic disparities in trauma mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies from the US have shown that quality of care is higher [8][9][10][11] and overall mortality is lower for severely injured patients at trauma centres with appropriate resuscitative, imaging, surgical and critical care facilities. [3][4][5][6][7] As a consequence, many countries across the developed world are now at various stages of developing trauma networks. [12][13][14] Common features of inclusive trauma networks include designation of specialist trauma centres, pre-hospital triage of severely injured patients 15 , agreed transfer protocols between network hospitals, and quality assurance programmes.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 There is consistent evidence, particularly from the United States, that inclusive trauma systems with designated trauma centres reduce mortality for severely injured patients. [3][4][5][6][7] The American College of Surgeons launched an accreditation programme for trauma centres in 1987. Observational studies from the US have shown that quality of care is higher [8][9][10][11] and overall mortality is lower for severely injured patients at trauma centres with appropriate resuscitative, imaging, surgical and critical care facilities.…”
Section: Introductionmentioning
confidence: 99%